Assessment of the ESC quality indicators in patients with acute myocardial infarction: a systematic review. (14th October 2021) - Masso Van Roessel, A; Perello Bordoy, A; Mas Llado, C; Ramis Barcelo, M; Vives Borras, M; Pons, J; Peral, V; Rossello, X
Abstract: Background: Quality indicators (QIs) provide a mechanism for measuring opportunities to improve cardiovascular care and outcomes. To help improving quality of care in patients with acute myocardial infarction (AMI), the European Society of Cardiology (ESC) set (in 2017) 20 QIs to evaluate several dimensions of care. These 20 QIs are organized in 3 areas and 7 domains defined in structural, performance measures including patient's feedback and outcomes. Several registries have reported their performance using real-world data, and some of them have reported that higher compliance is associated with lower mortality. There is a need to compile and summarize QI availability, feasibility and global compliance in real-world registries. Methods: A systematic review of PubMed and Web of Science was conducted including all original articles reporting the use of the ESC QIs in AMI patients. Methods and reporting follow the guidelines of the PRISMA Statement and the protocol was registered in PROSPERO (CRD42020190541). Inclusion criteria were studies providing original data, and studies evaluating the 2017 ESC ACVC set of QIs in patients with AMI (STEMI or NSTEMI). The main exclusion criterion was for non-original articles and studies evaluating a different set of QIs. Results: Among de 220 screened citations, 9 studies met the inclusion criteria after full-text review. Among these 9 studies, there were 11 different cohorts. Patients were recruited from 3 different continents (31 countries) between 2003 and 2018. The number of QIs assessed ranged from 6 to 20, with 5 studies (56%) reporting data for at least 75% of the 20 QIs. There was variability in the percentage of data availability with 4 QIs from 3 different cohort with limited data (2.4, 3.1, 3.2 and 6.1) and 13 QIs reported in 64% of the cohorts. We found that some publications were unable to provide the exact definition determined by the ESC ACVC working group, with 6 QIs with suboptimal definition (QIs 2.2, 5.1, 6.1, and the 3 QIs from domain 7). The rate of attainment had a great variation. In performance measures we found a higher level of compliance in the QIs 2.1, 4.3 and 5.2, and lower in 2.2 and 4.2. Conclusions: Our systematic review has shown that it is possible to measure most QIs in existing registries, and that there is room for improvement in terms of data availability, feasibility and levels of attainment to QIs. Our findings may influence the design of future registries to capture this information and help in QIs definition updates. In light of the experience accumulated from existing registries, there is a need to design registries and surveys specifically assessing QIs to have a more accurate picture. FUNDunding Acknowledgement: Type of funding sources: None.